Analisis Brand Awareness pada Coffee Shop Lokal - Matondang, Abigail Helena Evelyn; Setiyorini, Heri; Siswhara, Gita (Journal of Food and Culinary, 2025)
Coffee shops are currently popular places, especially among Generation Z. The large number of coffee shops today has led to fierce competition, requiring selective marketing strategies for coffee shops in a particular area. Brand awareness is an important factor for a business in order to establish a relationship between the brand and consumers.  This study aims to explore and analyze the development of brand awareness of local coffee shops and find out how coffee shops approach achieving brand awareness or becoming known to the coffee enthusiasts. This study uses a qualitative method. Data was collected through interviews and purposive sampling, resulting in 15 informants who met the research qualifications. The results show that there are many factors that influence brand awareness of local coffee shops in Bandung. The factors that influence brand awareness are social media and word of mouth, as well as other supporting factors that were found. Collaboration with communities, events, and campus organizations is an important strategy to expand consumer reach. These findings indicate that brand awareness can be formed by several factors, through the interaction of digital marketing strategies, positive consumer experiences, and social engagement that builds emotional closeness to the brand.